PAI MENTORING MODEL IN ATTITUDE IMPROVEMENT AND UNDERSTANDING OF ISLAMIC RELIGION SUBJECTS FOR STIA BANTEN STUDENTS - LUTFI, LUTFI (NIAGARA Scientific Journal, 2023)
The Mentoring of Islamic Education is one of development method as part of character and increment of insight perception. Islamic education mentoringhasbeen widely aplicated in several education institution such Primary High School till university level. Thisesearch focused on mentoring of islamic education subject for student of STIA Banten. by the limitation in focusing on the problem by submitting the research question in how the mentoring model of islamic education in STIA Banten, how the mentoring model of islamic education in STIA Banten carried out, and how the result of implementation of islamic education mentoring in STIA Banten. The Objective of this research is trying to find the mentoring method of PAI, effective and efficient concept at mentoring model of islamic education. This research used qualitative methode by compiling the data such as interview, observation, documentation and document analisis. The result show that 1). The design of educational of islamic education subject was not different with other subject, caused by both have had the same lesson plan which is could be implemented in learning process. 2). The mentoring model of islamic education has been technically changed in view of organizing, in which in the previous time being organized by academic and then organized by LDK STIA Banten. 3). The attitude changing of student had become more well mannered and more islamic, as well as had an advantage in academic aspect especially in islamic education subject. Thus, the existence of islamic education mentoring in university is positively needed by student. The conclusion of the research is that the mentoring model of islamic education is still relevant to be implemented in university. Along with it, there is still needed an evaluation of mentoring system progressively.